Biomarker Landscape in Neuroendocrine Tumors With High-Grade Features: Current Knowledge and Future Perspective - Prisciandaro, Michele; Antista, Maria; Raimondi, Alessandra; Corti, Francesca; Morano, Federica; Centonze, Giovanni; Sabella, Giovanna; Mangogna, Alessandro; Randon, Giovanni; Pagani, Filippo; Prinzi, Natalie; Niger, Monica; et al. (Frontiers in Oncology, 2022)
Neuroendocrine tumors (NETs) are classified based on morphology and graded based on their proliferation rate as either well-differentiated low-grade (G1) to intermediate (G2-G3) or poorly differentiated high-grade neuroendocrine carcinomas (NEC G3). Recently, in Gastroenteropancreatic (GEP) NETs a new subgroup of well-differentiated high-grade tumors (NET G3) has been divided from NEC by WHO due to its different clinical-pathologic features. Although several mutational analyses have been performed, a molecular classification of NET is an unmet need in particular for G3, which tend to be more aggressive and have less benefit to the available therapies. Specifically, new possible prognostic and, above all, predictive factors are highly awaited giving the basis for new treatments. Alteration of KRAS, TP53 and RB1 are mainly reported but also druggable alterations, including BRAF and H-MSI, have been documented in subsets of patients. In addition, PD-L1 demonstrated to be highly expressed in G3 NETs, probably becoming the new standard for G3 NEN discrimination and a predictive biomarker for immunotherapy. In this review we describe the current knowledge available on high grade NETs molecular landscape with a specific focus on those harboring a potentially therapeutic targets in the advanced setting.